Microsoft CloudMine: Data Mining for the Executive Order on Improving the Nation’s Cybersecurity - Herzig, Kim; Gostling, Luke; Grothusmann, Maximilian; Huang, Nora; Just, Sascha; Klimowski, Alan; Ramkumar, Yashasvini; McLeroy, Myles; Muslu, Kivanc; Sajnani, Hitesh; Vadaga, Varsha (2022)
Abstract to come...